Guilt Rules All : Irish Mystery, Detective, and Crime Fiction - Cliff, Brian; Mannion, Elizabeth (Lecturer) (Book collections on Project MUSE., 2020)
"Irish crime fiction, long present on international Best Seller lists, has been knocking on the door of the academy for a decade. With a varied mix of Irish Studies scholars providing comprehensive analyses on essential Irish detective series, Guilt Rules All: Mysteries, Detectives, and Crime in Irish Fiction establishes once and for all that this genre has arrived"--